Clinical and epidemiology evaluation of Aids-infected patients hospitalized between 2011 and 2016 in the Santos region of Brazil - Roberto Focaccia; Maria Luiza Alessi Ribeiro; Ana Carolina Carvalho Cossich; Raphael França Lacerda de Andrade; Karla Fabiana Begosso Sampaio da Fonseca Carbonari; Gabriela Amim Kallouf; Regiane Maria Rosa Vieira; João Pedro Lima Gemha; Aline Andruskevicius de Castro; Josiani Picin Correa de Oliveira; Flávio David Haddad Filho; Juliana Rocha Pinto Dias; et al. (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: We assessed the clinical-epidemiological profile of acquired immune deficiency syndrome (AIDS) patients in the Santos region (São Paulo state) with the highest AIDS prevalence in Brazil. METHODS Information was extracted from records of 409 AIDS-infected patients hospitalized between 2011 and 2016. RESULTS: Human immunodeficiency virus (HIV) was diagnosed in 24.7% of patients during admission, and 39.6% of already diagnosed patients received highly active antiretroviral therapy (HAART) irregularly. The mortality rate was 19.1%, and the main secondary manifestations were neurotoxoplasmosis and tuberculosis. CONCLUSIONS: AIDS patients in the Santos region had high rates of late diagnosis and low treatment adherence.